“String” type of barrierless plasma chemical reactor for generation ozone from air - Kudin, D.V.; Zavada, L.М.; Opalev, P.O.; Kotukov, O.V.; Khmelevska, V.F. (Вопросы атомной науки и техники, 2021)
The efficiency of ozone generation for barrierless plasma chemical reactors with different cathode designs was compared. The characteristics of ozone generation for a plasma chemical reactor with a string-type cathode in comparison with the previously developed star-shaped cathode for different combinations of bias and pulsed components of voltage have been investigated. The special feature of the operation of a plasma-chemical reactor with a string cathode is revealed. There is consisting in the absence of dependence of the transition of the discharge combustion mode into the spark breakdown phase from the presence of a bias voltage.